Effectiveness of Electroacupuncture and Electroconvulsive Therapy as Additional Treatment in Hospitalized Patients With Schizophrenia: A Retrospective Controlled Study - Jia, Jie; Shen, Jun; Liu, Fei-Hu; Wong, Hei Kiu; Yang, Xin-Jing; Wu, Qiang-Ju; Zhang, Hui; Wang, Hua-Ning; Tan, Qing-Rong; Zhang, Zhang-Jin (Frontiers in Psychology, 2019)
Electroacupuncture (EA) and electroconvulsive therapy (ECT) are often used in the management of schizophrenia. This study sought to determine whether additional EA and ECT could augment antipsychotic response and reduce related side effects. In this retrospective controlled study, 287 hospitalized schizophrenic patients who received antipsychotics (controls, n = 50) alone or combined with EA (n = 101), ECT (n = 55) or both (EA+ECT, n = 81) were identified. EA and ECT were conducted for 5 and 3 sessions per week, respectively, with a maximum of 12 sessions for ECT during hospitalization. The Scale for the Assessment of Positive Symptoms (SAPS) and Scale for the Assessment of Negative Symptoms (SANS) were used to assess the severity of psychotic symptoms. Clinical response on SAPS and SANS, weight gain, and adverse events were compared. Survival analysis revealed that the ECT and EA+ECT groups had markedly greater clinical response rate than controls on SAPS [72.7% and 90.1% vs. 64.0%; relative risk (RR), 1.974 and 2.628, respectively, P ≤ 0.004] and on SANS (67.3% and 70.4% vs. 42.0%; RR, 1.951 and 2.009, respectively, P ≤ 0.015). A significantly greater response rate on SANS than controls was also observed in the EA group (64.4% versus 42.0%; RR = 1.938, P = 0.008). EA-containing regimens remarkably reduced weight gain and incidences of headache, insomnia, dry mouth, and electrocardiographic abnormalities. These results suggest that EA and ECT can serve as additional treatment for enhancing antipsychotic response and reduce the side effects in hospitalized patients with schizophrenia.